"We're not your traditional police department." A qualitative implementation evaluation of a juvenile diversion program. (30th December 2022) - Barrett, James G.; Lee, Esther; Odayar, Varshini; Moyer, Margo; Cook, Benjamin Lê; Cortés, Dharma E.
Abstract: Youth in the juvenile criminal justice system experiencing mental health conditions are often neglected and offered few resources to seek treatment for behavioral health and substance use disorders. This leads to greater recidivism rates, pointing to the need for diversion programs that work directly with youth, family members, schools, and police. The primary objective of this study was to evaluate the Safety Net Program upon three implementation outcomes: acceptability, adoption, and appropriateness through qualitative interviews. Additionally, the study aims to amplify the stories of those with lived experiences, adding to the existing body of quantitative research in support of diversion models. Ten in‐depth semi‐structured qualitative interviews with police officers, school partners, and one parent were conducted to understand perspectives from the key stakeholders participating in the Safety Net model. The study found that integrating police officers in schools allows for the development of close relationships with students, families, and police which further facilitates better outcomes for youth.